Enhancing Learning through Post-Exam Review: A Case Study on Collaborative Coding Assessments - Ghosh, Arup; Skipper, Jakob (Proceedings of IEEE Southeastcon, 2024)
This paper discusses the outcomes and implications of conducting a post-exam review for students' learning of computer programming concepts in a collegiate setting. The post-exam review activity is implemented using a mix of metacognitive techniques including exam wrappers, peer grading, and the principles of self-directed learning. The activity consists of the class going through a document containing the anonymized code snippets that students submitted for an exam's programming problem(s). This document is generated from the Canvas exam using an application developed by the research team with the Node.JS framework. Students are tasked with analyzing the submissions one by one and then determining an appropriate grade by using a majority voting mechanism. With the use of a survey after the activity, the efficacy of the proposed approach was compared to that of classes taken by students which did not incorporate this approach and used a traditional way of grading.